2015
DOI: 10.33549/physiolres.932786
|View full text |Cite
|
Sign up to set email alerts
|

D-Galactose Induced Changes in Enzymatic Antioxidant Status in Rats of Different Ages

Abstract: Considering the preexisting influence of the process of natural aging on antioxidant enzymes activity and the level of lipid peroxidation, the age of the rats at which D-galactose (D-gal) treatment is started could strongly impact the development of D-gal induced senescence. To evaluate this, we subjected 1, 3 and 15 months old rats to D-gal treatment in parallel with having appropriate placebos (0.9 % saline). Our results showed elevated glutathione peroxidase (GPx) activity and no significant changes in supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…All of these results have been confirmed by the hepatic histopathological examination as dilatation and congestion were detected in the central as well as the portal veins with inflammatory cells infiltration in the portal zone and degeneration in the hepatocytes all over the parenchyma. ese findings were in accordance with [38,38]. Treatment with D. salina carotenoids showed amelioration of the histopathological examination of the liver tissues exhibiting almost Advances in Pharmacological and Pharmaceutical Sciences normal hepatic lobules with an average sized central vein, while zeaxanthin showed thick-walled attenuated blood vessels with preserved hepatic architecture than appeared sections isolated from rats treated with polar fractions.…”
Section: Discussionsupporting
confidence: 84%
“…All of these results have been confirmed by the hepatic histopathological examination as dilatation and congestion were detected in the central as well as the portal veins with inflammatory cells infiltration in the portal zone and degeneration in the hepatocytes all over the parenchyma. ese findings were in accordance with [38,38]. Treatment with D. salina carotenoids showed amelioration of the histopathological examination of the liver tissues exhibiting almost Advances in Pharmacological and Pharmaceutical Sciences normal hepatic lobules with an average sized central vein, while zeaxanthin showed thick-walled attenuated blood vessels with preserved hepatic architecture than appeared sections isolated from rats treated with polar fractions.…”
Section: Discussionsupporting
confidence: 84%
“…4B ). d -galactose has been extensively leveraged in mouse models of ageing 32 , 33 . Therefore, the accumulated excessive d -galactose in BM could exert a negative effect on BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose d -galactose can induce premature ageing of astrocytes, foetal fibroblasts and neuroblasts 32 , 34 . A number of reports have suggested that the ageing model induced by d -galactose is associated with oxidative stress 33 . Subsequent studies have demonstrated that ROS accumulation mainly accounts for this process 23 .…”
Section: Discussionmentioning
confidence: 99%
“…D-gal-induced aging is associated with oxidative stress and AGE generation [ 43 ]. ROS play key roles in this process as their accumulation leads to the induction and maintenance of cellular senescence [ 44 ].…”
Section: Discussionmentioning
confidence: 99%